An Aegean History and Archaeology Written through Radiocarbon Dates. (17th August 2020) - Katsianis, Markos; Bevan, Andrew; Styliaras, Giorgos; Maniatis, Yannis
This dataset is the outcome of an INSTAP-funded project "An Aegean Prehistory Written in Radiocarbon Dates". It includes 3159 14C dates from 353 sites in Greece and reflects an attempt to exhaustively collect and cross-check all published radiocarbon dates from existing databases, original publications and preliminary reports using both international and Greek sources (376 sources in total). Although originally targeting prehistoric dates, all dates coming from archaeological or environmental sampling were integrated in the final dataset regardless of chronological period. Sites have been identified and positioned as accurately as possible, while additional information on sampling procedures, sample material and stratigraphic context have been recorded.